Gomphus indicus, a new species of Gomphaceae from Northwestern Himalayas of Jammu and Kashmir, India - Singh, Shiny; Verma, Komal; Kumar, Sanjeev; Sharma, Yash Pal (Phytotaxa, 2024)
Gomphus indicus is proposed here as a new species based on morphological characteristics and phylogenetic analyses of the nuclear rDNA internal transcribed spacer and large subunit of the rDNA region. The combination of morphological and molecular data confirmed the novelty of the species and its infrageneric placement within the genus Gomphus Pers. This species was found in association with Cedrus deodara (Roxb. ex D. Don) G. Don and Abies pindrow (Royle ex D. Don) Royle and is characterized by infundibuliform to flabelliform pileus with wavy irregular margins, greyish yellow to light yellow, wrinkled rugose pileus surface, cylindrical to bacilliform large basidiospores (15–21.5 × 6–8 µm) with irregular isolated warts, the absence of hymenial cystidia, and pileipellis composed of thin-walled, loosely interwoven hyphae. A detailed description, illustrations, and comparisons with morphologically similar and related taxa are provided here. Additionally, a worldwide key to the globally known species of Gomphus is also provided.